The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1063/5.0010558
|View full text |Cite
|
Sign up to set email alerts
|

Rheology of a dilute suspension of deformable microswimmers

Abstract: Suspensions of swimming microorganisms play important roles in biology, medicine, and engineering. To predict and control the flow field of such suspensions, an understanding of their rheological properties is required. In this background, the suspension rheology of various types of microorganisms has been investigated intensively. Research has shown that some microorganisms, such as ciliates, deform when a strong force is exerted on their bodies. However, the effect of cell deformability on suspension rheolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…The role of body deformability on active suspensions and their effective rheology remains a generically open area of inquiry, but simulations have revealed that the sign of the effective medium's second normal stress differences depends on body stiffness (224). Other non-Newtonian features due to active suspensions like viscoelasticity (11,220,225,226) and yield-stress behavior (227,228) have also been predicted.…”
Section: Complex Rheologymentioning
confidence: 99%
“…The role of body deformability on active suspensions and their effective rheology remains a generically open area of inquiry, but simulations have revealed that the sign of the effective medium's second normal stress differences depends on body stiffness (224). Other non-Newtonian features due to active suspensions like viscoelasticity (11,220,225,226) and yield-stress behavior (227,228) have also been predicted.…”
Section: Complex Rheologymentioning
confidence: 99%
“…The role of body deformability on active suspensions and their effective rheology remains a generically open area of inquiry, but simulations have revealed that the sign of the effective medium's second normal stress differences depends on body stiffness (222). Other non-Newtonian features due to active suspensions like viscoelasticity (11,218,223,224), and yield-stress behavior (225,226) have also been predicted.…”
Section: Complex Rheologymentioning
confidence: 99%